Effect of build direction on the microstructure evolution and their mechanical properties using GTAW based wire arc additive manufacturing. (May 2022) - Tripathi, Umashankar; Saini, Nitin; Mulik, Rahul S.; Mahapatra, Manas Mohan
Abstract: In recent years, welding-based wire-arc additive manufacturing has been enthusiastically accepted to fabricate different parts of structural materials. In this study, a gas tungsten arc welding-based wire-arc additive manufacturing setup was developed, and a low-carbon alloy steel ER 70S-6 filler wire was used to fabricate a geometry. To analyze the mechanical properties of the printed alloy, room temperature tensile test, hardness and Charpy toughness tests are produced. The microstructure reveals a mostly homogeneous ferrite phase as a matrix and a small amount of pearlite phase at grain boundaries, except for the last build surface. The grain size was found to be doubled from middle build to last build surfaces. The tensile test results show isotropic tensile properties in both directions. The observed morphological features of the fractured surfaces in both directions were found to be in good agreement with their tensile test results, confirming a higher ductility across the build samples. Large scatter was observed in the hardness tests concerning the building direction. Graphical Abstract: ga1